The effect of the characteristics of audit committees on internal control: an empirical study of the French context / Abdelhakim Ben Ali nd Amine Bakkeri - Ben Ali, Abdelhakim; Bakkeri, Amine (UiTM Press, 2021)
This article reports on an empirical study of Société des Bourses Françaises (SBF)'s 250 French companies on the list of the Paris Stock Exchange over the period 2012-2018. It focused on the characteristics of audit committees, examined the interaction between audit committees and the internal quality control system. Panel data was the framework used for this research. Data was collected manually from annual reports and reference documents. After a selection procedure we obtained a sample of 162 French companies and a total of 1134 observations of company years. Data analysis indicated that financial expertise, independence, frequency of meetings, and size of the audit committees positively and significantly impacted internal control weaknesses. Likewise, women's participation in audit committees was significantly correlated with the mitigation of internal control problems. This research enriches the current debate on the effectiveness of internal control bodies within companies and demonstrates ways to enhance audit committees implement quality control. Unavailability of data, the size, and the choice of companies selected for this sample constitute the shortcomings in this research. While these limitations can reduce the explanatory power of the model presented, they can serve as a basis for future research.